Development of the Adult Compassion Scale - Nas, Eşref; Sak, Ramazan (Fırat University, 2022)
In the Turkish literature, although there are some scales adapted from another language to Turkish and used to measure the compassion levels of adults, no measurement tool has been found that was developed in Turkey and serves this purpose. Considering this shortcoming, it has been seen that it is important and necessary to develop a valid and reliable measurement tool that can determine the compassion levels of adults. In this context, it was aimed to develop a culturally appropriate and original Adult Compassion Scale in this study. The participants of the study consisted of 808 adults over the age of 18. Twenty items were grouped under four factors (Behavioral Compassion, Emotional Compassion, Cognitive Compassion, and Motivational Compassion) based on the exploratory factor analysis, and this four-factor structure explained 64.95% of the total variance. This four-factor structure was tested with Confirmatory Factor Analysis and it was found that the obtained fit values (?2/sd= 2.291; RMSEA=.057, RMR=.024, IFI=.95, CFI=.95, NFI=.92, RFI=.90, GFI=.91, AGFI=.89, SRMR=.060) showed good agreement. The internal consistency coefficient of the Compassion Scale for Adults was determined as .92 for the total scale, .90 for Behavioral Compassion, .83 for Emotional Compassion, .81 for Cognitive Compassion, and .85 for Motivational Compassion sub-dimensions. As a result, it was seen that the Compassion Scale developed to determine the compassion levels of adults is a valid and reliable measurement tool.

Türkçe alanyazında, başka bir dilden Türkçeye uyarlanmış, yetişkinlerin merhamet düzeylerini ölçmeye yarayan bazı ölçekler bulunmakla birlikte, Türkiye’de geliştirilmiş ve bu amaca hizmet eden herhangi bir ölçme aracına rastlanmamıştır. Bu eksiklik göz önünde bulundurulduğunda yetişkinlerin merhamet düzeylerini saptayabilecek geçerli ve güvenilir bir ölçme aracının geliştirilmesinin önemli ve gerekli olduğu görülmüştür. Bu bağlamda, bu çalışmada kültüre uygun ve orijinal bir Yetişkin Merhamet Ölçeği’nin geliştirilmesi amaçlanmıştır. Çalışmanın katılımcılarını 18 yaş üstü 808 yetişkin oluşturmuştur. Yapılan Açımlayıcı Faktör Analizi sonucunda 20 maddenin dört faktör (Davranışsal Merhamet, Duygusal Merhamet, Bilişsel Merhamet, Motivasyonel Merhamet) altında toplandığı ve bu dört alt boyutlu yapının toplam varyansın %64.95’ini açıkladığı anlaşılmıştır. Ayrıca dört faktörlü yapının Doğrulayıcı Faktör Analiziyle test edilmesi sonucunda saptanan uyum değerlerinin (?2/sd= 2.291; RMSEA=.057, RMR=.024, IFI=.95, CFI=.95, NFI=.92, RFI=.90, GFI=.91, AGFI=.89, SRMR=.060) iyi uyum gösterdikleri görülmüştür. Geliştirilen ölçeğin iç tutarlılık katsayısı alt boyutlarda; Davranışsal Merhamet için .90, Duygusal Merhamet için .83, Bilişsel Merhamet için .81, ve Motivasyonel Merhamet için .85 olarak hesaplanmış olup, ölçeğin toplamı için .92 olarak belirlenmiştir. Sonuç itibariyle, yetişkin bireylerin merhamet düzeylerini belirlemek amacıyla geliştirilen Yetişkin Merhamet Ölçeği’nin geçerli ve güvenilir bir ölçme aracı olduğu tespit edilmiştir.
YETİŞKİN MERHAMET ÖLÇEĞİNİN GELİŞTİRİLMESİ